PENGEMBANGAN LEMBAR KERJA SISWA FISIKA BERBASIS PROBLEM BASED LEARNING UNTUK MENINGKATKAN PARTISIPASI DAN HASIL BELAJAR SISWA SMA KELAS X - Algiranto Algiranto (Jurnal Perspektif Pendidikan, 2021)
This study aims to (1) produce PBL-based physics worksheets that are suitable to be used to increase student participation and learning outcomes, (2) examine the increase in participation and learning outcomes of class X students using PBL-based worksheets, and (3) examine the responses of class X students. X after using PBL-based worksheets. This research is a research and development (R & D) using a 4D model, namely define, design, develop, and disseminate. The results of this study are (1) PBL-based physics worksheets are feasible to increase participation and learning outcomes for high school students in class X with very good assessment and reliability based on the alpha coefficient value in LKS I, II, which is 0.935 (special) , 0.972 (special) and the correlation value between raters in LKS I, II is 0.877 (special), 0.946 (special), (2) the increase in student participation and learning outcomes is shown by the standard gain value of 0, respectively. 09 (low) and 0.5 (medium), (3) student responses after using PBL-based physics worksheets were 4.17 and 4.23 both categorized as good.